(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the nutritional, biological, and technological basis for the use of pumpkin and sesame seeds as unconventional plant components in cottage cheese products. The literature indicates that cottage cheese is a highly digestible dairy product rich in protein, calcium, and phosphorus, and that fortifying it with plant-derived bioactive compounds is a promising approach for the development of functional foods. Pumpkin contains carotenoids, polyphenols, tocopherols, minerals, and dietary fiber, which can enhance the vitamin-mineral value and antioxidant potential of the product. Sesame seeds, in turn, are a valuable source of protein, calcium, vitamin E, dietary fiber, and lignans, and therefore can improve the biological value of cottage cheese products. Available studies suggest that pumpkin additives influence color, flavor, aroma, and viscosity of curd systems, making dosage optimization essential. Sesame ingredients, when applied at moderate levels, can improve texture, protein content, and sensory quality, whereas excessive inclusion may worsen flavor and color acceptability. Therefore, the rational incorporation of pumpkin and sesame into a cottage cheese matrix can provide a functional product with improved nutritional value and acceptable organoleptic properties.